PERLINDUNGAN HUKUM TERHADAP AHLI WARIS DALAM SENGKETA HARTA BERSAMA PASCA PUTUSNYA PERKAWINAN: ANALISIS YURIDIS NORMATIF - Jauharoh; Fitria Agustin (PT. Saha Kreasi Indonesia, 2026)
This study aims to analyze the legal protection of heirs in disputes over marital joint property following the dissolution of marriage from the perspective of positive law in Indonesia. A common issue arising in practice is the lack of clarity in distinguishing between joint property and inherited assets, which often triggers conflicts between the surviving spouse and other heirs. This research employs a normative juridical method with statutory and conceptual approaches, supported by primary and secondary legal materials. The results indicate that, normatively, the regulation of joint property and inheritance has been clearly stipulated in legislation. However, in practice, there remains a gap between legal norms and their implementation, caused by differences in interpretation, lack of proof of ownership, and low public legal awareness. This condition results in the suboptimal legal protection of heirs. This study emphasizes that the effectiveness of legal protection depends not only on the existence of regulations but also on the understanding and application of the law by society and law enforcement officials. Therefore, it is necessary to strengthen legal implementation, improve public legal literacy, and optimize dispute resolution mechanisms to achieve legal certainty and justice.